Exploring Literary Interpretation through Extensive Reading: A Reader Response Perspective on Rosenblatt’s Transactional Theory - Purwani, Wilujeng Asih (UICELE, 2026)
This study aimed to analyse the implementation of extensive reading with a reader-response technique in developing students’ literary text interpretation skills in the context of English as a Foreign Language. If Extensive Reading more often discusses increasing fluency and reading motivation, there is still very limited discussion about Extensive Reading that focuses on reader responses with transactional theory in literary interpretation. Students construct personal interpretations using texts of their own choosing both classical and modern literary text. Data collection was conducted through observation, in-depth interviews and recording in the form of reflection journals (Book Response Form) and student projects. The data were analysed by theme analysis approaches to determine patterns of response, reading strategies and growth of students’ interpretation skills. The results of the study suggest that the adoption of extensive reading based on literary texts with a reader-response strategy is effective to boost students’ interest in reading, motivate active involvement in learning, and create deeper interpretive abilities students not only understand the literal meaning, but are also able to discern latent meanings. However, this study also indicated that the limitations of vocabulary and the awareness of cultural context are still the key impediments in reading. This research concludes that the integration of extensive reading and reader-response approach is an effective strategy in improving the interpretation ability of literary texts of EFL students